The Effect of Inductive- Deductive Approach on Students’ Mathematical Creative Thinking Ability and Self-Efficacy - Cecep Mahmudin; Utari Sumarmo; Asep Kustiana (IKIP Siliwangi, 2020)
This research was a pre test-post test experimental control group design having a goal to analyze the role of Inductive-Deductive Approach (IDA) on improving students’ mathematical creative thinking ability (MCTA) and self efficacy (MSE). Subjects of this research were 70 eleventh grade students from two classes selected purposively in a Senior High School in Garut. Instruments of this research were a MCTA test, and a MSE scale. The research found that the role of IDA was greater than the role of scientific approach (SA) on improving students’ MCTA and MSE. Students getting treatment with IDA approach obtained MCTA and MSE at good grades qualification. While students taught by SA attained MCTA and MSE at low-moderate grades level. Apart of those findings, the research found that students getting treatment with IDA encountered a litle bit difficulty in solving MCTA tasks. In contrast students taught by SA experienced in allmost items of MCTA tasks. In addition, the research also found there was no assocition between MCTA and MSE and students performed good and active learning during IDA lessons.Keyword: mathematical creative thinking, mathematical self efficacy, model eliciting activities (IDA)